EVALUASI KUALITAS LAYANAN JASA PADA BENGKEL OTOMOTIF RODA EMPAT - Bertu Pabuntang; Johan S C Neyland; Trytia Arungpadang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2020)
Customer satisfaction and dissatisfaction with a service or goods are usually determined by how a product is received by the customer from the service provider or product so that if the service provided in accordance with the expectations of the customer then they will feel satisfied and vice versa. This research aims to find out the attributes of the company that can provide satisfaction and dissatisfaction for customers who use repair services in car repair works using the Important Performance Analysis (IPA) method.From the results of research conducted in one of the workshop car repair service providers gave the result that the company needs to improve the attributes that exist in quadrant 1 namely kecepatan service working time,, kecepatan service claims,ketetapan service complaints vehicle, waktu wait waiting time before getting service officer,keramahan in serving customers, responsibility of the workshop for the service provided, pengecekan vehicle in detail and karyawan master the services offered so that in the future these attributes can provide satisfaction to customers.Keywords : customer satisfaction,service, Importance Performance Analysis (IPA)